PEMETAAN KOPERASI BERDASARKAN ICIS DAN DAYA SAING DI EKS KARESIDENAN BESUKI JAWA TIMUR - Moehammad Fathorrazi, ; Hadi Paramu, ; Mohamad Dimyati, (Pendidikan Ekonomi, 2010)
This study was intended to make a mapping of cooperatives in ex- Besuki region using  ICA Grid  Model, recommended by International Cooperative Alliance.  A module of supervision and development was then composed based on the mapping. The data were elicited with questionnaires.  The sample was selected with a proportional stratified random sampling technique. The findings reveal that the average of cooperatives in Jember municipality was at quadrant I, meaning that the cooperatives were ideal, whereas cooperatives in Bondowoso were poor because most of them were at quadrant II.  By average, the cooperatives in Situbondo were also at quadrant II, meaning that they had implemented cooperative principles but they remained uncompetitive. Furthermore, the cooperatives in Banyuwangi were relatively better than those in Bondowoso and Situbondo.